PENGARUH ROUTING PROTOCOL SWITCH MULTILAYER UNTUK TRANSFER DATA PADA JARINGAN KOMPUTER - Sajati, Haruno; Sudaryanto, Sudaryanto (Jurnal Nasional Teknologi Komputer, 2022)
The results of the QoS parameters based on the average total throughtput on the Cisco Catalyst 3750 Switch Multilayer device show a value of 81.4579Mbps greater than the Cisco 2800 Router, while the average total packetloss on the Cisco Catalyst 3750 Switch Multilayer device shows a value of 0.0739% more smaller than the Cisco 2800 Router while the total average delay on the Cisco Catalyst 3750 Switch Multilayer device shows a value of 3.8090ms which is smaller than the Cisco 2800 Router. Based on the results of the Mann-Whitney comparison of 3 test variables between the Cisco Catalyst 3750 Switch Multilayer and Cisco 2800 Router devices at =0.05, it is said that there is no significant difference between the throughput, packetloss and delay values obtained